Morphometric Characterization of Parasite Varroa Sp. of Bee Apis Mellifera L. In Benin - Aude, Kelomey Eminsede; Armand, Paraiso; Francois, Azonwade; Charlemagne, Gbemavo; Georg, Goergen; Manuelle, Tamo; Lamine, Baba-Moussa (European Scientific Journal, ESJ, 2016)
Varroa sp. is one of the most important pests of world of bees A. mellifera Linnaeus (Hymenoptera: Apidae). The aim of this study is to analyze the morphological variability of Varroa so as to identify the different morphotypes of V. destructor. The study was conducted in 24 localities and 24 municipalities located in three regions (North-East, North-West and the Centre) of Benin. One to two hives were randomly selected per locality for collecting samples. In total 46 Varroa were examined in this study. Analysis of variance components was used to determine the share of the variability of morphological characteristics of V. destructor based on localities and climatic zones. Numerical classification was performed to group the populations of V. destructor based on morphological descriptors. The results show that the variability of morphological descriptors of V. destructor is usually larger at the community level than in climatic zones. In total four morphotypes of V. destructor are distinguished in Benin through the 4 variables used in the study.